A latent class approach for sepsis diagnosis supports use of procalcitonin in the emergency room for diagnosis of severe sepsis (2013)
ABSTRACT: Background: Given the acknowledged problems in sepsis diagnosis, we use a novel way with the application ofthe latent class analysis (LCA) to determine the operative characteristics of C-reactive protein (CRP), D-dimer (DD)and Procalcitonin (PCT) as diagnostic tests for sepsis in patients admitted to hospital care with a presumptiveinfection.Methods: Cross-sectional study to determine the diagnostic accuracy of three biological markers against the goldstandard of clinical definition of sepsis provided by an expert committee, and also against the likelihood of sepsisaccording to LCA. Patients were recruited in the emergency room within 24 hours of hospitalization and werefollow-up daily until discharge.Results: Among 765 patients, the expert committee classified 505 patients (66%) with sepsis, 112 (15%) withinfection but without sepsis and 148 (19%) without infection. The best cut-offs points for CRP, DD, and PCT were7.8 mg/dl, 1616 ng/ml and 0.3 ng/ml, respectively; but, neither sensitivity nor specificity reach 70% for anybiomarker. The LCA analysis with the same three tests identified a “cluster”of 187 patients with severalcharacteristics suggesting a more severe condition as well as better microbiological confirmation. Assuming thissubset of patients as the new prevalence of sepsis, the ROC curve analysis identified new cut-off points for the testsand suggesting a better discriminatory ability for PCT with a value of 2 ng/ml.Conclusions: Under a “classical”definition of sepsis three typical biomarkers (CRP, PCT and DD) are not capableenough to differentiate septic from non-septic patients in the ER. However, a higher level of PCT discriminates aselected group of patients with severe sepsis.